Design and fabrication of small scale automatic fish dryer machine - Muhammad Syazwan Bin Durahman (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Dried fish is a fish without salt. It is a hot dry with temperrature and wind. Drying is one of the tradition fod preservaion method before using freezing technology,The dried fish could survive and kept some years. Strorage of dried fish also should not wet and dry to maintain the quality of dried fish